Avaliação dos efeitos do tratamento com ravuconazol em combinação com anlodipino na infecção experimental por Trypanosoma cruzi - Machado, Yara Almeida (2018)
Chagas disease, caused by the protozoan Trypanosoma cruzi, affects about 8 million individuals. There is no effective and safe treatment for the chronic phase of the infection, which motivates the search for new therapeutic alternatives. In this way, drug combination is a promising strategy, especially when using drugs already approved for clinical use. Ravu is an antifungal that has potent trypanocidal activity in vitro and in vivo, however it is not effective in inducing parasitological cure in monotherapy. Amlodipine (Anlo) is a calcium channel blocker widely used as antihypertensive and previous studies have demonstrated its trypanosomicidal activity. In the present study, the effects of Ravu and Anlo combinations on experimental T. cruzi infection by Y strain were evaluated. Initially, in vitro studies were conducted to investigate the cytotoxic potential of the combinations for mammals cells and to identify the nature of the interaction between the drugs on different forms of the parasite. For in vivo evaluations, Swiss mice, experimentally infected or not were treated p.o. for 20 consecutive days with suboptimal doses of ravuconazole (2.5 and 5 mg / kg) alone and in combination with 10 mg / kg amlodipine. The response to treatment was evaluated considering the following parameters: parasitemia suppression and reactivation, mortality and detection of parasite DNA at 60 days after treatment. Also, the influence of the treatments on the cytokine profiles and humoral response were evaluated. The results showed that there was no additional toxicity resulting from the combined use of the drugs in vitro and the interaction profile between Ravu and Anlo was dependent of the parasite stage, being antagonistic on trypomastigote forms and synergistic when considering intracellular amastigotes. Murine model studies showed that drug combinations were well tolerated in the absence or presence of the infection. High levels of parasitemia and a 50% mortality rate were detected in infected and untreated mice. The Ravu administration, alone or in combination, induced a drastic reduction in parasitism, with suppression of parasitemia during all the treatment period, protecting the animals from mortality. Anlo when used alone was effective in reducing the number of trypomastigote forms detected at the peak of parasitemia, but did not reduce mortality. Interestingly, the combination treatments were effective in increasing cure rates two to four times when compared to Ravu monotherapies, evidencing a positive interaction between the drugs in vivo. Anti-T. cruzi IgG plasma levels confirmed these findings, with a drastic reduction in the amount of antibodies up to 60 days after treatment. In addition, the cytokine profile from infected and treated animals was similar to that identified for healthy mice. The results allow concluding that there is a beneficial effect resulting from the combination of Ravu with Anlo in the treatment of acute experimental infection by T. cruzi Y strain